Evaluating the effects of smartphone racing games and other game types on pedestrian's risk-taking inclinations. (November 2018) - Chen, Ping-Ling; Pai, Chih-Wei
Abstract: Objectives: Past studies have concluded that racing games may induce car drivers' risk-taking behaviours. Limited research has been conducted to investigate whether such an effect applies to pedestrians when crossing a street. This study investigates the effects of smartphone racing games on pedestrian's risk-taking inclinations. Materials and Methods: Using WiFi video cameras, pedestrians' risk-taking inclinations such as game playing when crossing the street, red-light violation, and walking outside the crosswalk at a signalised intersection in Taipei City were observed. Data such as their phone features, smartphone game types, and personal attributes were obtained in the interviews conducted after pedestrians had completed crossing the street. Effects of racing games (RCG) were compared with those of several other games (e.g., Pokemon, RPG: Role-Playing Game, ACT: Action Game, SPG: Sports Game, FTG: Fighting Game, STG: Shooting Game, PZG: Puzzle Game, ETC: Other Game). Results: A total of 1480 participants completed crossing the street and were interviewed between April 2017∼March 2018. Pokemon Go was most associated with game playing when crossing, running the red light, and walking outside the crosswalk. Logistic regression models reveal several other important determinants of risk-taking inclinations: being a student, larger smartphone screen size, unlimited Internet allowance. Student players of Pokemon GO, and playing Pokemon with unlimited Internet allowance, appear to contribute to pedestrian's risk-taking inclinations. Conclusions: RCG appears not to be associated with pedestrian's risk-taking behaviours as much as Pokemon Go does. Instead, compared to other smartphone games, Pokemon Go is most associated with pedestrian's risk-taking inclinations. Highlights: Playing Pokemon Go is most associated with pedestrian's risk-taking behaviours. Racing game is ranked as the 2nd important factor to induce red-light violation. Student players of Pokemon Go are a determinant of risk-taking behaviours. Larger smartphone screen size and unlimited Internet allowance are risk factors.